Penerapan Teknik Sinematografi Dalam Pembuatan Video Promosi Dejavu Barbershop - Syafrizal, Agusdi; Firjatullah; Bustomi, Tommy (LPPMPP Yayasan Sejahtera Bersama Bengkulu, 2025)
Dejavu Barbershop faces challenges in maximizing promotional appeal amidst increasingly fierce industry competition. Dejavu Barbershop currently uses social media by posting simple pictures and videos of haircut results. However, this method has not been able to attract maximum attention amid increasingly fierce competition. This research aims to increase the attractiveness of promotions through making videos with aspects of Cinematographic Techniques namely composition, camera angle, shot type, camera movement, lighting, and editing, using the Multimedia Development Life Cycle (MDLC) method which includes six stages: concept, design, material collection, creation, testing, and distribution. The results of the research are in the form of a promotional video for Dejavu Barbershop with a duration of 1 minute 30 seconds published through the POLNES Multimedia Informatics Engineering YouTube platform. Based on the questionnaire results, this romotional video with Cinematography Techniques was rated very well by respondents, with a total percentage of 90.39%. In addition, this promotional video has a positive impact on sales at Dejavu Barbershop after the video is published, with an increase in the number of customers and sales figures. Keywords—Promotional Video, Barbershop , Cinematography